Bacterial biofilm in silver-impregnated contact lens cases. Issue 4 (August 2020) - Vijay, Ajay Kumar; Zhu, Hua; Willcox, Mark; Ketelson, Howard; Stapleton, Fiona
Abstract: Purpose: This study investigated the efficacy of pre-conditioning lens cases on bacterial biofilm formation and removal. Methods: Silver impregnated (MicroBlock / ProGuard™ & i-Clean) and control storage cases were pre-conditioned for 24 h with their respective multipurpose solutions (MPDSs). Cases were then inoculated with 2 ml of 10 6 CFU/mL of ocular isolates of either P. aeruginosa or S. aureus and incubated for 48 h. Cases were subsequently disinfected (4−6 hours) as per the manufacturer's recommended disinfecting time (MRDT) followed by the recommended case hygiene procedures - recapping wet (MicroBlock / ProGuard™ cases only) or rinse and air-dry or rinse, tissue-wipe and air dry (mechanical disruption). Surviving bacteria were enumerated using standard techniques. Results: Pre-conditioning the MicroBlock / ProGuard™ cases with MPDS significantly reduced biofilm formation (-1.1 log10 CFU, p < 0.01 for P. aeruginosa & -1.3 log10, p < 0.001, CFU for S. aureus ) compared to the i-Clean lens cases. Maintaining the MicroBlock / ProGuard™ lens cases wet after the MRDT resulted in partial removal of bacterial biofilms (-2.9 log10 CFU, p < 0.001 for P. aeruginosa and -2.6 log10 CFU, p < 0.001 for S. aureus ). Air-drying of all three types of lens storage cases after MRDT significantly reduced the bacterial biofilm (-5.4 log10 CFU, p < 0.001 for P. aeruginosa and -3.5 log10 CFU, p < 0.001 for S. aureus ). Mechanical disruption produced the greatest reduction in the levels of bacterial biofilm in all 3 types of lens cases tested (-6.8 log10 CFU, p < 0.001 for P. aeruginosa and -4.5 log10 CFU, p < 0.001 for S. aureus ). Synergi MPDS was significantly better than AQuify MPDS in removing bacterial biofilm from all 3 lens case types for case hygiene treatments with an air-drying step. Conclusion: Pre-conditioning of silver-impregnated ProGuard™ lens cases inhibited initial bacterial biofilm formation. Synergi MPDS was more effective than AQuify MPDS in removing bacterial biofilm in silver impregnated cases and tissue-wiping significantly improved biofilm removal.